The use of weasel words as disclaimers in superiority claims / Kamisah Ariffin...[et. al.] - Ariffin, Kamisah; Razali, Azlini; Nikman, Khairunisa; Baharum, Norzie Diana; Abd Wahab, Rahimah (Universiti Teknologi MARA Cawangan Pahang, 2013)
Issues reported in the news regarding the false claims of products, particularly beauty and health products, suggest that consumers may have been misled and deceived by the claims made by the advertisements on the products. Data from a study on the print advertisements on the local complementary and alternative medicines in Malaysia show that the most frequently used technique in claiming the superiority of these products is the use of weasel words. These words are able to make the products more appealing to the consumers. However, consumers may not realize that weasel words are empty words that function as modifiers to qualify the claim. In fact, the words are cleverly used to negate the claim or as disclaimers to the claim. This paper focuses on the use of these words in advertisements in the local CAM print advertisements in Malaysia with the aim of educating consumers of the advertisers’ trick of the trade. Using Mallery’s framework of the types of weasel words (words of action, words of comparison, words of possibility, and words of illusion of strength), the analysis indicates the presence of 527 weasel words in the 157 advertisements examined, with the action words being the most commonly used. The analysis also reveals that the highest number of weasel words is found in the biology-based products, followed by the energy-based products, whole medical systems and body-based practices. It is hoped that by recognizing the types of weasel word and how it functions in a claim, consumers may be more discerning in evaluating the claim of the product.